MENINGKATKAN KEUNGGULAN BERSAING PERUSAHAAN DENGAN MENGELOLA PROSES ANTRIAN - Ria Satyarini (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
Companies can achieve competitive advantage by several way, such as by managing queues. A queue can define by a line of waiting customers who require or need service from a server or company. The waiting customer can be satisfied or dissatisfied by the queuing systems that company use. Managing queues means that company tries to diminish the negative effect of waiting, so we can exceed the customer expectation and we have the happy customer. Keyword: Queue, psychology of waiting, competitive advantage, differentiation.